The efficacy of augmented reality technology assisted by 3D-CT reconstruction in microvascular decompression for hemifacial spasm craniotomy - Hailiang Shi; Kuo Zhang; Yang Li; Haowei Shi; Xiaolong Wen; Tao Qian (BMC Surgery)
Abstract Background We aimed to assess the efficacy of augmented reality technology assisted by three-dimensional (3D) computed tomography (CT) reconstruction, in facilitating microvascular decompression (MVD) during craniotomy for hemifacial spasm. Methods A retrospective analysis was conducted on 80 patients who underwent MVD for hemifacial spasm at Hebei General Hospital between January 2, 2020, and March 24, 2021. Among them, 43 patients received traditional craniotomy (assigned to the traditional group), while 37 patients underwent modified craniotomy (assigned to the modified group). The distinctive feature in the modified group involved employing 3D-CT reconstruction assisted by augmented reality technology, specifically utilizing Sina software, for precise localization of scalp incision. The impact of the modified method on surgery was assessed based on operation time, incision length, postoperative complications, long-term efficacy, and patient-reported outcomes. Results No significant differences in age, sex, disease duration, and disease side were observed between the two groups (P > 0.05). The modified group exhibited a significantly shorter average craniotomy time (29.68 ± 4.89 min vs. 34.19 ± 4.55 min, P < 0.001) and time to close the skull (25.22 ± 3.12 min vs. 28.95 ± 2.54 min, P < 0.001) compared to the traditional group. Additionally, the incision length in the modified group (59.69 ± 10.71 mm) was evidently lower than that in the traditional group (70.84 ± 11.27 mm, P < 0.001). The overall rate of any postoperative complication was significantly lower in the modified group (5.4%) compared to the traditional group (23.3%; P = 0.018). While overall immediate postoperative complication rates were not statistically different, the modified group showed a trend towards fewer complications, particularly no CSF leakage. At 1-year follow-up, the modified group had a lower spasm recurrence rate (2.7% vs. 7.0%, P = 0.348), significantly lower postoperative pain scores at 7 days (VAS: 2.8 ± 0.9 vs. 3.6 ± 1.1, P = 0.002), and higher patient satisfaction (94.6% vs. 86.0%, P = 0.184). Conclusion Employing 3D-CT reconstruction assisted by augmented reality technology in MVD for hemifacial spasm significantly improves surgical efficiency, is associated with favorable long-term outcomes, and enhances patient-reported satisfaction, suggesting its potential value for clinical application and potentially contributing to enhanced safety, particularly in reducing specific complications like CSF leakage.